2000
DOI: 10.3109/01674820009075621
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of labor/ delivery complications and infant birth weight: A prospective multivariate study

Abstract: Using a multidimensional approach to measure stress, this study prospectively examined the influence of maternal stress, social support and coping styles on labor/delivery complications and infant birth weight. Beginning in the third month of pregnancy, stress was assessed monthly. In each trimester, data on social support, coping strategies, lifestyle behaviors and pregnancy progress were collected. One month following delivery, information on labor, delivery and infant status was obtained. The final sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 47 publications
3
62
0
4
Order By: Relevance
“…Meanwhile, there is already clear evidence that the impact of the economic crisis on the European populations is modulated by the degree of social development and cohesion of the country, and by the governmental policies adopted in response to the crisis and preserve public welfare (Kaplan, 2012;Karanikolos et al, 2013;Suhrcke et al, 2009). Studies have confirmed that adequate emotional and social support during pregnancy acts as a buffer of the material and psychological impact of adverse economic conditions on foetal growth (Aarts and Vingerhoets, 1993;Hoffman and Hatch, 1996;Feldman et al, 2000;Da Costa et al, 2000), even more efficiently than resources (Rini et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is already clear evidence that the impact of the economic crisis on the European populations is modulated by the degree of social development and cohesion of the country, and by the governmental policies adopted in response to the crisis and preserve public welfare (Kaplan, 2012;Karanikolos et al, 2013;Suhrcke et al, 2009). Studies have confirmed that adequate emotional and social support during pregnancy acts as a buffer of the material and psychological impact of adverse economic conditions on foetal growth (Aarts and Vingerhoets, 1993;Hoffman and Hatch, 1996;Feldman et al, 2000;Da Costa et al, 2000), even more efficiently than resources (Rini et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Today, more than 5000 years later, women still have an array of negative feelings and emotions that accompany pregnancy and delivery. These may have detrimental effects on both maternal and neonatal pregnancy outcomes such as preterm delivery, cesarean section (CS) and maternal depression after birth, among others [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite rapid medical advances improving health outcomes, the incidence of pregnancy complications, including low birth weight, has changed very little since the 1960's (Da Costa, et al, 2000). The traditional examination of biomedical and demographic risk has proven unsuccessful in identifying all women at high risk for adverse outcomes (Da Costa, et al, 1998;Molfese, et al, 1987).…”
Section: Problem Identificationmentioning
confidence: 99%
“…Stress can be indirectly related to poor birth outcomes by leading to unhealthy behaviors such as poor nutrition, smoking, alcohol, illicit or inappropriate drug use (Da Costa, Brender, & Larouche, 1998;Da Costa, Dritsa, Larouche, & Brender, 2000;March of Dimes, 1999;Walker, Cooney, & Riggs, 1999;, depression, sedentary lifestyles, and withdrawal from family and friends. Another variable affecting outcomes is whether the pregnancy is planned or unplanned, wanted or unwanted (Sable & Wilkinson, 2000;.…”
Section: Introductionmentioning
confidence: 99%